Internet-Based Sex-Seeking Behavior Promotes HIV Infection Risk: A 6-Year Serial Cross-Sectional Survey to MSM in Shenyang, China. (25th December 2016) - Pan, Shi; Xu, Jun-Jie; Han, Xiao-Xu; Zhang, Jing; Hu, Qing-Hai; Chu, Zhen-Xing; Hai, Yan-Qiu; Mao, Xiang; Yu, Yan-Qiu; Geng, Wen-Qing; Jiang, Yong-Jun; Shang, Hong
Abstract : HIV prevalence is still rapidly increasing among Chinese men who have sex with men (MSM). The Internet also makes it easier for MSM to have casual partners. This study aims to evaluate the trend of Internet-based sex-seeking behavior of MSM and its impact on HIV prevalence, the distribution of HIV subtype strains, and transmitted drug resistance rates. A serial cross-sectional study was conducted from 2009 to 2014. Of the 1, 981 MSM, 50.5% (1, 000/1, 981) mainly sought homosexual partners through the Internet (Internet-based MSM, IBM). The proportion of IBM among total MSM subjects increased from 43.3% to 61.5% (p < 0.001 ). HIV prevalence of IBM increased from 5.7% to 20.7%, while that of non-Internet-based MSM (NIBM) increased from 7.0% to 14.7%. A relative higher proportion of NIBM were infected with HIV CRF01_AE subtype than IBM (79.5% versus 72.2%, p = 0 . 52 ). Multivariable analysis found IBM had a significantly higher HIV prevalence than NIBM (13.2% versus 10.5%, aOR = 1.4, 95% CI [1.0–1.9]). Being a migrant non-Shenyang resident MSM (aOR = 1.9, 95% CI [1.3–2.9]) and occasionally/never using condoms with casual homosexual partners (aOR = 1.7, 95% CI [1.1–2.6]) were two distinct risk factors for HIV infection in IBM. More efforts should be targeted towards developing interventions aimed at IBM, particularly migrant MSM and who engage in UAI with casual homosexual partners.